2000
DOI: 10.1126/science.289.5486.1931
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Mutations in Mitochondrial DNA by tRNAs Imported from the Cytoplasm

Abstract: Mitochondrial import of a cytoplasmic transfer RNA (tRNA) in yeast requires the preprotein import machinery and cytosolic factors. We investigated whether the tRNA import pathway can be used to correct respiratory deficiencies due to mutations in the mitochondrial DNA and whether this system can be transferred into human cells. We show that cytoplasmic tRNAs with altered aminoacylation identity can be specifically targeted to the mitochondria and participate in mitochondrial translation. We also show that huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
96
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 23 publications
5
96
0
2
Order By: Relevance
“…One could suggest therefore that inhibited or perturbed translation (appearance of additional translation products) is due to a decrease of imported tRK1. This is in agreement with our previous observation of suppression of a mtDNA mutation by imported tRNAs (Kolesnikova et al 2000) and with a more recent hypothesis suggesting the need of several cytoplasmic tRNAs to provide a complete decoding in yeast mitochondria (Rinehart et al 2005). It may occur that we obtained here the first evidence that, at least at higher temperature, tRK1 is recruited by mitochondrial translation machinery.…”
Section: Enolase Another Protein With Multiple Functionssupporting
confidence: 82%
See 1 more Smart Citation
“…One could suggest therefore that inhibited or perturbed translation (appearance of additional translation products) is due to a decrease of imported tRK1. This is in agreement with our previous observation of suppression of a mtDNA mutation by imported tRNAs (Kolesnikova et al 2000) and with a more recent hypothesis suggesting the need of several cytoplasmic tRNAs to provide a complete decoding in yeast mitochondria (Rinehart et al 2005). It may occur that we obtained here the first evidence that, at least at higher temperature, tRK1 is recruited by mitochondrial translation machinery.…”
Section: Enolase Another Protein With Multiple Functionssupporting
confidence: 82%
“…Mitochondrial functions of tRK1 are not completely clear, although our previous results demonstrated that its mutant versions are functional in mitochondrial translation, since they are able to suppress a nonsense mutation in mitochondrial DNA-localized gene (Kolesnikova et al 2000). tRK1 import is highly specific, since the second cytosolic tRNA Lys UUU (tRK2) is not imported (Entelis et al 1998).…”
mentioning
confidence: 99%
“…Nucleoside modifications are a universal feature of tRNAs, necessary for fine-tuning the tRNA structure for translational efficiency and in a few cases modifications even change the tRNA amino acid specificity (Muramatsu et al+, 1988a(Muramatsu et al+, , 1988bWeber et al+, 1990)+ Although in various organisms specific modifications at certain positions in a particular tRNA show phylogenetic conservation, only a few positions and/or modifications are highly conserved (Auffinger & Westhof, 1998)+ These include the 39 CCA, pseudouridine (⌿) at position 55, and the unmodified pyrimidine at position 33 (uridine in 97% of the cases; Sprinzl et al+, 1998a)+ Unlike RNA modification, editing of tRNAs has been observed in several eukaryotes ranging from protists to metazoans (Lonergan & Gray, 1993;Yokobori & PÀÀbo, 1995Marechal-Drouard et al+, 1996;Antes et al+, 1998;Price & Gray, 1999;Lavrov et al+, 2000)+ RNA editing typically restores base pairing at various positions in the tRNA molecule, regenerating conserved structural motifs important for tRNA processing and function+ In cases where tRNA editing alters the anticodon sequence, enzymatic deamination of adenosine to inosine is the common mechanism and it helps expand the base-pairing ability of the tRNA codonanticodon interaction (Auxilien et al+, 1996;Gerber & Keller, 1999)+ Two instances of cytidine (C)-to-uridine (U) alterations of the anticodon sequences of tRNAs have also been reported+ In marsupials, a single C-to-U editing event in the second position of the anticodon changes the decoding properties of a mitochondriaencoded tRNA Asp (Janke & PÀÀbo, 1993), and in Leishmania tarentolae, the single nucleus-encoded tRNA Trp is imported into the mitochondrion and undergoes C-to-U editing at the wobble position, thereby allowing decoding of UGA codons as tryptophan (Alfonzo et al+, 1999)+ In many organisms, a set of nucleus-encoded tRNAs is imported into the mitochondria (Schneider & Marechal-Drouard, 2000)+ The number of imported tRNAs varies from a single tRNA in yeast (Kolesnikova et al+, 2000) to all mitochondrial tRNAs in trypanosomatids (Simpson et al+, 1989;Hancock & Hajduk, 1990)+ Little is known about the extent, nature, or function of nucleotide modifications of such imported tRNAs+ Modification of U33 in mitochondrial (mt) tRNA Tyr and C32 in mt tRNA Lys and tRNA Leu in Trypanosoma brucei has been reported, but the nature of these modifications was not established …”
Section: Introductionmentioning
confidence: 99%
“…A more direct strategy to treat diseases caused by hmt-tRNA mutations is to import functional tRNAs into mitochondria. Pioneering studies by Tarassov and colleagues (34,35) demonstrated that an altered yeast cytoplasmic tRNA Lys can be imported into human mitochondria in vitro and in vivo. The imported tRNA participates in mitochondrial protein synthesis and partially rescues a pathogenic mutation in hmt-tRNA Lys .…”
mentioning
confidence: 99%